Web-Based CLIL for Oracy Development: A Case Study in Engineering Education - Aflahatun, Nur; Mujiyanto, Januarius; Wuli Fitriati, Sri; Pratama, Hendi (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This paper was intended to explore how web-based Content and Language Integrated Learning (CLIL) was used as a task and a tool for oracy growth in mechanical engineering education. The participants were purposively selected to represent varying levels of CLIL engagement and English proficiency, consisting of one English instructor and three second-semester mechanical engineering students from Pancasakti University, Tegal. Data were collected via semi-structured interviews and document analysis of lesson plans, followed by thematic analysis to interpret the findings. The results showed that web-based CLIL improved students' spoken English skills and helped them to understand engineering ideas by means of real-time films, simulations, and online materials. Moreover, various challenges persisted, particularly at Common European Framework of Reference for Languages (CEFR) levels A2–B1, where they hindered comprehension, language production, and equitable digital access. To foster more inclusive and effective CLIL implementation, this paper highlighted the need for explicit scaffolding strategies, dual-focused assessment rubrics, and thoughtful syllabus revision. The findings highlighted the need of professional development and lecturer facilitation in maximizing the incorporation of CLIL for oracy in engineering environments.